Resilience Profile of Students with Single Parents - Nurhayati; Rici Kardo; Rahmawati Wae (Global Action and Education for Society, 2026)
This research is motivated by students who often appear gloomy and lack interaction with their peers, as these students are sensitive to their family's financial problems. This study aims to describe the resilience profile of students with single parents as seen from: 1) the ability to control emotions, 2) the ability to bounce back from problems, and 3) independence and decision-making skills. The type of this research is descriptive quantitative. The population of this study consists of 30 respondents. The sampling technique used is purposive sampling with a sample size of 30 respondents. The instrument used in this study is a questionnaire. The data analysis in this study is in percentage. The results of this study show: 1) The ability to control emotions in students with single parents at SMA Negeri 13 Padang is in the very high category. 2) The ability to bounce back from problems in students with single parents at SMA Negeri 13 Padang is in the very high category. 3) Independence and decision-making ability in students with single parents at SMA Negeri 13 Padang is in the very high category. Therefore, it is recommended for guidance counselors to utilize various innovative and interactive educational media, such as short videos and role-playing, to develop students' resilience.